The Theoretical Foundations of Incorporating Islamic Beliefs in a Stress Inoculation Program for Muslims (American Journal of Islam and Society, 1991)
Little data are available about the nature of stress which Muslims inNorth America frequently endure. Muslim scholars have not attempted todefine the major stressors these Muslims experience, nor have they furnishedMuslims with an inocuIation program that integrates Islamic beliefs withcognitive techniques in order to change stress quality and quantity. Thedevelopment of such a program, however, is not possible without theoreticalfoundations that employ the findings of stress research. On the other handsuch a theory, if fuIly deveIoped, is not functional without empirical datato sustain its basic propositions.Hence, the purpose of this paper is to: a) develop the theoreticalfoundations of the interreIationship between stress cognition and Islamic beliefs;b) present a stress cognition paradigm that explains the moderation functionof certain Islamic beliefs; and c) incorporate certain Islamic beliefs in theapplication of the cognitive techniques of stress management.The Relationship between Stress Cognitionand Religious BeliefsStress is defined as the outcome of the cognitive process through whicha person interprets and attaches meaning(s) to an event. Selye (1974) explainsit as being the negative or positive cognitive appraisal that causes the individualto perceive an event as stressful. Based on the outcomes of the cognitiveappraisal, Selye distinguishes between two types of stress: a) distress orpathogenic stress “which goes beyond people’s optimum arousal point so thatperformance and health deteriorate” (Savery 1986, 17), and b) eustress, which ...